The acute psychobiological impact of the intensive care experience on relatives. Issue 1 (2nd January 2016) - Turner-Cobb, J.M.; Smith, P.C.; Ramchandani, P.; Begen, F.M.; Padkin, A.
Abstract : There is a growing awareness amongst critical care practitioners that the impact of intensive care medicine extends beyond the patient to include the psychological impact on close family members. Several studies have addressed the needs of relatives within the intensive care context but the psychobiological impact of the experience has largely been ignored. Such impact is important in respect to health and well-being of the relative, with potential to influence patient recovery. The current feasibility study aimed to examine the acute psychobiological impact of the intensive care experience on relatives. Using a mixed methods approach, quantitative and qualitative data were collected simultaneously. Six relatives of patients admitted to the intensive care unit (ICU) of a District General Hospital, were assessed within 48 h of admission. Qualitative data were provided from semi-structured interviews analysed using interpretative phenomenological analysis. Quantitative data were collected using a range of standardised self-report questionnaires measuring coping responses, emotion, trauma symptoms and social support, and through sampling of diurnal salivary cortisol as a biomarker of stress. Four themes were identified from interview: the ICU environment, emotional responses, family relationships and support. Questionnaires identified high levels of anxiety, depression and trauma symptoms; the most commonly utilised coping techniques were acceptance, seeking support through advice and information, and substance use. Social support emerged as a key factor with focused inner circle support relating to family and ICU staff. Depressed mood and avoidance were linked to greater mean cortisol levels across the day. Greater social network and coping via self-distraction were related to lower evening cortisol, indicating them as protective factors in the ICU context. The experience of ICU has a psychological and physiological impact on relatives, suggesting the importance of identifying cost-effective interventions with evaluations of health benefits to both relatives and patients.